A PHONETIC CONTRASTIVE ANALYSIS OF ENGLISH WORDS IN THREE JAPANESE SONGS BY AKB48 - Harwintha Y. Anjarningsih; Anisa Saraayu (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
Many studies have revealed how Japanese speakers pronounce English words differently. However, not much research has explained the causes of the difference, let alone relating such difference with native language interference. By drawing a comparison between the sound structures of the English and Japanese languages using Contrastive Analysis Hypothesis (CAH), we will see how native language may influence foreign language usage and cause pronunciation differences in popular songs. Transcriptions of three AKB48’s songs – Heavy Rotation, Sugar Rush, and Namida Surprise – will be used as the data sources to determine native language interference. Our findings show that additions of vowel sounds, changes of syllable, changes of height and place of vowel articulation, replacements of a consonant with another consonant, and elisions of consonants happened to the English words across the three songs. These phonetic changes should inform discussions about the relationship between lyrics and melody in songs that incorporate two or more languages (i.e., bilingual).